2021
DOI: 10.1155/2021/7245566
|View full text |Cite|
|
Sign up to set email alerts
|

Deep Learning-Based Cervical Spine Posterior Percutaneous Endoscopic Disc Nucleus Resection for the Treatment of Cervical Spondylotic Radiculopathy

Abstract: In the past 10 years, the technology of percutaneous spine endoscopy has been continuously developed. The indications have expanded from simple lumbar disc herniation to various degenerative diseases of the cervical, thoracic, and lumbar spine. Traditional surgery for the treatment of cervical radiculopathy includes anterior cervical decompression surgery, anterior cervical decompression plus fusion surgery, and posterior limited fenestration surgery. This article mainly studies the treatment of cervical spond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In scientific articles, the terms "intervertebral canal" and "intervertebral foramen" were sometimes synonymous [2]. Thorough examination of the lateral structures of the cervical part of the vertebral column made it possible to assess the peculiarities of the shape and size of the transverse processes and intervertebral foramen, to designate the lateral aperture and to describe the anatomical entities involved in the formation of the canal walls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In scientific articles, the terms "intervertebral canal" and "intervertebral foramen" were sometimes synonymous [2]. Thorough examination of the lateral structures of the cervical part of the vertebral column made it possible to assess the peculiarities of the shape and size of the transverse processes and intervertebral foramen, to designate the lateral aperture and to describe the anatomical entities involved in the formation of the canal walls.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical manifestation of dystrophic diseases of the cervical part of the vertebral column depends on its anatomical features and pathological changes [1]. In particular, the pathogenesis of radicular syndrome is associated with dystrophy of the intervertebral discs and connective tissue elements of the spine, and of compression of the spinal nerves by fibrous and bony overgrowths [2,3]. At the same time, the clinical manifestations of the disease do not always correspond to the diagnosed morphological changes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the anterior approach has less room for exposure and, accordingly, minimal bleeding without damaging large vessels. For the posterior approach, the muscle tissue behind the vertebral body is more developed, the structure is close, the blood supply is more abundant, and there are more small vessels [ 11 ]. Although the structure is simple, it takes more time to better expose the operation site and control the amount of blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the various mechanisms of cervical spinal cord injury, a range of surgical methods can be used. Anterior [ 10 ] or posterior approach decompression resection [ 11 ] is a common surgical method for the treatment of cervical spondylosis and has also been gradually applied in the treatment of cervical spinal cord injury. Decompression surgery can release pressure on the spinal cord with edema after injury, and the timing of surgery is particularly important to optimize recovery.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%